Dialogue of Christian Eco-Theology with Hindu Cosmology in the Disruption Era - Daniel Syafaat Siahaan (International Journal of Interreligious and Intercultural Studies, 2020)
Global citizens of the world are entering a new era, the era of disruption. Terminologically, disruption means the era of chaos or the era of the disturbance. In the Indonesian dictionary, disruption is interpreted as being uprooted from the root. In the era of disruption, nothing is certain and established. The rapid development of information technology has a big influence on this era. This causes the level of local and global competition and competition among individuals or even countries becomes a necessity. Recently the situation of the Americans and Iran has heated up. Indonesia and China also. In a competition, superior-inferior relations become necessary. In such situations, the preservation of nature becomes the most easily ignored, or even sacrificed. For a moment, in competition between individuals or between countries to prove their superiority, nature became the most powerless and inferior. If the balance of nature is disturbed, the most disadvantaged are humans as well as animals. Forest and land fires in Australia are conclusive evidence. When nature is disturbed, humans and animals are the first victims to feel the loss. This issue is the background of the writing of this research. This research seeks to elaborate on the Christian eco-theology notion and to dialogue it with the Hindu cosmology notion. The method used is qualitative research with a comparative study approach. This research is expected to contribute ideas and also enriching the Christian eco-theological dialogue with Hindu cosmology in the era of disruption, in particular concerning the environment.